(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2025)
Background: ISARIC/WHO 4C Mortality Score is a risk stratification tool that helps predict the in-hospital mortality of COVID-19 patients. However, this tool was developed and validated in a British population, and thus, the external validation of this tool in local populations is important. This study aimed to analyze the outcome of COVID 19 patients using 4C Mortality Score in the COVID unit of Bangladesh Institute of Tropical and Infectious Diseases (BITID) Chattogram. Materials and methods: This hospital-based prospective observational study included 115 admitted adult patients with a confirmed diagnosis of COVID-19 by RTPCR method. Patients under age of 18 and those with missing data in any of the components of ISARIC 4C score were excluded from study. Relevant sociodemographic and clinical data were collected, and the 4C mortality score was calculated at admission. Outcome measures were need for oxygen therapy, mode of oxygen therapy, and in-hospital mortality. Results: Mean age of the patients was 50.6±18.4 years in the present study and 47.8% were male. The median ISARIC 4C mortality score was 7.0 (Interquartile range: 3-12) and at the time of admission 31 (27%), 34 (29.6%), 33 (28.7%), and 17 (14.8%) patients were in low, intermediate, high, and very-high risk groups, respectively. The mortality was 10.4%, the area under the curve of the score was 0.921 (95% Confidence Interval [CI]: 0.868-0.974, p < 0.001) and the cutoff value correctly classified 83.5% of the patients. The cutoff value of >11 had sensitivity, 91.67% (95% CI: 61.52-99.79); specificity, 82.52% (95% CI: 73.79-89.30), positive predictive value, 37.93% (95% CI: 20.69-57.74), and negative predictive value, 98.84% (95% CI: 93.69-99.97). There was a significant moderate positive correlation between admission 4C mortality score and length of stay in hospital for the surviving patients (Pearson correlation coefficient=0.514, p<0.001). Conclusion: The ISARIC score was found to have excellent predictive ability for mortality in hospitalized COVID-19 patients in our Bangladeshi cohort. Despite recent advances in the treatment and management of adults hospitalized with COVID-19, 4C mortality score can continue to inform clinical decision making. Chatt Maa Shi Hosp Med Coll J; Vol.23 (1); January 2024; Page 61-67